A Novel Approach to Evaluate the Benefits of Casing Treatment in Axial Compressors. (14th June 2012) - Legras, Guillaume; Trébinjac, Isabelle; Gourdain, Nicolas; Ottavy, Xavier; Castillon, Lionel
Abstract : Passive control devices based on casing treatments have already shown their capability to improve the flow stability in axial compressors. However, their optimization remains complex due to a partial understanding of the related physical mechanisms. In order to quantitatively assess the interaction between slots and the blade tip flow, the present paper develops a novel analysis methodology based on a control-volume approach located in the rotor tip region. This methodology may be used for analyzing the casing treatment based on both axi- and non-axisymmetric slots design. The second issue of the paper focuses on the application of the current approach to better understand the effects of axi- and non-axisymmetric grooves in three different axial compressors which differ by the flow regime (subsonic/transonic) and the smooth casing shape (cylindrical/concave). Numerical simulations are performed, and results of the current approach with and without casing treatments are compared.